Multifaceted leaders: the double-edged sword effect of narcissistic leadership on employees’ work behavior - Chen, Hao; Zhang, Lei; Wang, Liang; Bao, Jiaying; Zhang, Zihan (Frontiers in Psychology, 2024)
So far, most studies have focused on exploring the negative effects of narcissistic leadership. However, little attention has been paid to whether narcissistic leadership also has a positive effect. This study is based on Conservation of Resources Theory and reveals that narcissistic leadership has a double-edged sword effect. Through the analysis of 450 employees and their direct leaders' pairing data collected in three stages, it is found that: narcissistic leadership has a positive effect on employee' hostility toward supervisor and psychological availability; hostility toward supervisor mediates the relationship between narcissistic leadership and counterproductive work behavior; psychological availability mediates the relationship between narcissistic leadership and organizational citizenship behavior; in addition, environmental uncertainty enhances the positive effect of narcissistic leadership on employee' hostility toward supervisor and psychological availability, which in turn moderates the indirect effect of narcissistic leadership on counterproductive work behavior through employee' hostility toward supervisor and on organizational citizenship behavior through psychological availability.